1987
DOI: 10.1002/jrs.1250180308
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of and phase transitions in caesium hydrogen sulphate

Abstract: The Raman and infrared spectra of the superionic protonic conductor CsHS04(CsDS04) were investigated in the 18450 K range. Polarized single crystal Raman and infrared reflection spectra were also studied at room temperature. An assignment of bands due to internal and external vibrations is given in terms of symmetry species and approximate type of motion. The spectroscopic results, in particular the behaviour of the Raman bands as a function of temperature, are used to discuss the crystalline structures of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 18 publications
6
34
0
Order By: Relevance
“…The structural results indicate no possiblity of the Cs ÷ diffusion as reported elsewhere (Pham-Thi, Colomban, Novak & Blinc, 1987). Haynovskiy, Pavlyuhin & Hayretdinov (1985) reported that in the low-temperature phase the conductivity of CsHSO4 is two orders of magnitude higher than that of CsDSO4, whilst in the superionic phase their conductivities are approximately equal.…”
Section: Csdso4supporting
confidence: 58%
See 3 more Smart Citations
“…The structural results indicate no possiblity of the Cs ÷ diffusion as reported elsewhere (Pham-Thi, Colomban, Novak & Blinc, 1987). Haynovskiy, Pavlyuhin & Hayretdinov (1985) reported that in the low-temperature phase the conductivity of CsHSO4 is two orders of magnitude higher than that of CsDSO4, whilst in the superionic phase their conductivities are approximately equal.…”
Section: Csdso4supporting
confidence: 58%
“…Haynovskiy, Pavlyuhin & Hayretdinov (1985) reported that in the low-temperature phase the conductivity of CsHSO4 is two orders of magnitude higher than that of CsDSO4, whilst in the superionic phase their conductivities are approximately equal. From this arose tlte assumption that the diffusion of Cs ÷ contributes to the conductivity (Pham-Thi, Colomban, Novak & Blinc, 1987). However as noted above the room-temperature structure of CsHSO4 differs from that of CsDSO4 and so the large difference in conductivity in the lowtemperature phases of protonated and deuterated samples cannot be solely assigned to an isotopic effect as previously stated (Haynovskiy, Pavlyuhin & Hayretdinov, 1985).…”
Section: Csdso4mentioning
confidence: 84%
See 2 more Smart Citations
“…We distinguish the (AsO ) by the intense Raman band at about 767 cm\, and by the shoulder and the intense infrared bands near 760 and 782 cm\, respectively. Yet the vibration is not degenerated ( (a )), which is why this weak splitting is not to the crystal "eld, but to the coexistence of two H AsO\ and H AsO constituting the dimer (H AsO HAsO H )\ (26,27). By analogy with M H(SO ) (M"Na, K, Rb, and NH ) (28,29), the band with high frequency is attributed to the H As(2)O\ group ( (H As(2)O\ )), whereas the one with low frequency is correlated to the H As(1)O4 group ( (H As(1)O )).…”
Section: Characterizationmentioning
confidence: 98%